Distortions to Agricultural versus Nonagricultural Producer Incentives - Anderson, Kym (2012)
For more than a century, government policies have grossly distorted resource use in agriculture, both within and between countries. Earnings from farming in many developing countries have been depressed by a pro-urban bias in own-country policies as well as by governments of richer countries favoring their farmers with import barriers and subsidies. Both sets of policies reduce national and global economic welfare and inhibit economic growth; they also add to inequality and poverty in developing countries. Since the 1980s, however, numerous developing and some high-income country governments have reduced their sectoral and trade policy distortions. This paper draws on new empirical studies to show the changing extent of policy distortions to prices faced by the world's farmers since the 1950s. Modeling results provide an indication of how far those reforms proceeded between the early 1980s and 2004 and of how much scope remains for removing continuing inefficiencies in global agricultural resource use.